Two Big Distortions: Bank Incentives for Debt Financing - Jesse Groenewegen; Peter Wierts (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
Systemically important banks are subject to at least two departures from the neutrality of debt versus equity financing: the tax deductibility of interest payments and implicit funding subsidies. This paper fills a gap in the literature by comparing their mechanism and interaction within a common analytical framework. Findings indicate that both the tax shield and implicit funding subsidy remain large, in the order of up to 1 percent of GDP, despite decreases in recent years. But the underlying mechanisms differ. The tax shield incentivises debt financing as it reduces tax payments to the government. The implicit funding subsidy incentivises debt financing as it lowers private bankruptcy costs. This funding subsidy is passed on to other bank stakeholders. It therefore provides incentives for increases in balance sheet size and risk taking. This, in turn, increases the value of the tax shield. Overall, these results help to explain why systemically important banks are highly leveraged.
Keywords: G21; G32; H25; 330; taxation; subsidies; debt; leverage